Cancel Culture dalam Perspektif Etika Islam: Analisis Moralitas Publik di Era Media Digital - Abdus Salam; Isroqunnajah Isroqunnajah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article examines the phenomenon of cancel culture in the digital media era through the lens of Islamic ethics. Cancel culture, which refers to collective public punishment through social ostracism, online shaming, and reputational destruction, has become a dominant form of moral judgment in contemporary digital interactions. This study uses a conceptual and library research approach by analyzing classical and contemporary Islamic ethical principles, including adab al-ikhtilāf, ḥusn al-ẓann, al-amr bi al-ma‘rūf wa al-nahy ‘an al-munkar, and norms of public morality in Islamic scholarly tradition. The findings indicate that while Islam encourages accountability, moral correction, and the protection of public interest, the practices within cancel culture often contradict Islamic ethical values due to excessive blame, character assassination, absence of verification, and mob-based judgment. The study highlights that Islamic ethics emphasizes proportionality, restorative justice, and moral responsibility rather than punitive social destruction. Therefore, cancel culture reflects a crisis of moral communication rooted in digital anonymity, emotional amplification, and weakened ethical boundaries. This article concludes that Islamic ethical principles can provide a more humane, just, and constructive framework for addressing wrongdoing in digital spaces, preventing moral excesses while promoting responsible public discourse. Keywords: Cancel culture, digital ethics, Islamic ethics, moral judgment, public morality.